The problems of the reorganization of the police security guard in the Tersk region in the political discourse of the regional and district boards in 1911-1913 - Inna M. Dabagova (Кавказология, 2025)
The article is devoted to the problems of the reorganization of the police security guard in the Tersk region in the political discourse of the regional and district boards in 1911-1913.  In the course of the work, the instructions of the head of the Tersk region to the heads of districts and departments, reports of the heads of districts and departments to the regional chief, reports of the head of the region to the regional board, drafts of new staff of the Tersk police security guard, etc. were analyzed. The law "on the temporary change of the staff of the administration of the districts of the Tersk region" dated December 29, 1911 is analyzed. The proposals of the heads of districts and departments of the Tersk region (including the head of the Nalchik district) to improve the effectiveness of the Tersk police security guard, the need to modernize it and increase its staffing are described. The report of the head of the Tersk region to the Tersk regional government on the transformation of the police unit dated September 11, 1912, compiled taking into account the opinions of the heads of districts and departments, is analyzed in detail. It is concluded that the opportunity of the heads of districts and departments of the Tersk region to participate in the discussion of the issues of the transformation of the Tersk Security Guard and the development of its staff represented an important step in strengthening state power and ensuring the safety of the population in the region.